2021
DOI: 10.11604/pamj.2021.39.135.29171
|View full text |Cite
|
Sign up to set email alerts
|

Public willingness to adhere to COVID-19 precautionary measures in Sudan: an application of the Health Belief Model

Abstract: Introduction coronavirus disease (COVID-19) is a highly infectious disease caused by the novel coronavirus (SARS-CoV-2). Several public health and social protective measures that may prevent or slow down the transmission of COVID-19 were introduced. However, these measures are unfortunately being neglected or deliberately ignored by some individuals. Methods a cross sectional online based survey was conducted to identify possible factors influencing public willingness t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…(2020) (47) (51) highlighted that willingness to comply to COVID-19 preventive measures were considerably associated with all constructs of the HBM.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) (47) (51) highlighted that willingness to comply to COVID-19 preventive measures were considerably associated with all constructs of the HBM.…”
Section: Discussionmentioning
confidence: 99%
“…The mean ± SD age of the study participants was 24.7 ± 4.1 years and the majority of the participants were in the age group of 23-27 years. This nding is supported by a study conducted in Sudan where the mean ± SD age of the participants was 26.7 ± 7.95 and the majority (83.2%) of the participants were in the age group of 20-40(13). The ages are typical of the majority of the students enrolled in undergraduate programs in Tanzania.…”
mentioning
confidence: 57%
“…19 Moreover, a study in Sudan showed that 87.2% of the general population were willing to adhere to COVID-19 preventive measures. 20 The difference in reported adherence to COVID-19 precautionary measures between counrties could be due to the extent and outreach of awareness raising campaigns and health education programs implemented in different contexts.…”
Section: Discussionmentioning
confidence: 99%